Evaluation of Women Empowerment Services By Government from 2000-2013 (A Case Study of Sargodha Division) - Ishaque Ahmed,; Yasir Javed,; Saqib Aziz Sani,; Zeeshan Munawar,; Malik Kaleem Ullah, (Al-Qanṭara, 2024)
The present study was conducted to find out the evaluation of women empowerment services by government from 2000-2013. Service basically refers to action taking for help other or facilitates other and empowerment refers to make someone enable and bring him/her in mainstreaming. Major objective of the study was to assess the effectiveness of the government services given by the governmental institutions that taking into account the empowerment of receiver women and analyze the after and before condition of women that are the beneficiaries. By nature, research was quantitative, self-structured interview schedule were used for the collecting of information. A sample of 240 respondents was taken from the division Sargodha. Multi-stage sampling method was used for the collection of data. At first stage researcher select Sargodha city purposely. At second stage researcher select four Tehsils (Sargodha, Sahiwal, Shahpur, Bhalwal) randomly by using chit method. At third stage from each tehsil one vocational training institution was selected conveniently. At fourth stage 60 respondents were taken from each vocational training institution conveniently. In this way a sample of 240 respondents were taken. Data were analyzed by using Statistical Package for Social Sciences (SPSS) version 16.0. It was found that women were very much satisfied with the services given by vocational training institutions and they feel considerable change in their life after getting training. Furthermore, these training make them enable and independent and enhance their decision making power.